The central nervous system during lung injury and mechanical ventilation: a narrative review. (October 2021) - Albaiceta, Guillermo M.; Brochard, Laurent; Dos Santos, Claudia C.; Fernández, Rafael; Georgopoulos, Dimitris; Girard, Timothy; Jubran, Amal; López-Aguilar, Josefina; Mancebo, Jordi; Pelosi, Paolo; Skrobik, Yoanna; Thille, Arnaud W.; et al.
Summary: Mechanical ventilation induces a number of systemic responses for which the brain plays an essential role. During the last decade, substantial evidence has emerged showing that the brain modifies pulmonary responses to physical and biological stimuli by various mechanisms, including the modulation of neuroinflammatory reflexes and the onset of abnormal breathing patterns. Afferent signals and circulating factors from injured peripheral tissues, including the lung, can induce neuronal reprogramming, potentially contributing to neurocognitive dysfunction and psychological alterations seen in critically ill patients. These impairments are ubiquitous in the presence of positive pressure ventilation. This narrative review summarises current evidence of lung–brain crosstalk in patients receiving mechanical ventilation and describes the clinical implications of this crosstalk. Further, it proposes directions for future research ranging from identifying mechanisms of multiorgan failure to mitigating long-term sequelae after critical illness.